Pengaruh Aplikasi Actinomycetes terhadap Serangan Fusarium oxysporum Schlecht. f.sp. cepae (Hanz.) Synd. et Hans. Penyebab Penyakit Layu pada Bawang Merah (Allium ascalonicum L. var. Mentes) - Mia Rahmiyati; Shinta Hartanto; Ni Wayan Hari Sulastiningsih (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
Fusarium oxysporum Schlecht. f.sp. cepae (Hanz.) Synd. et Hans. is a fungus that causes Fusarium wilt in shallots, which causes damage to tubers and reduces yields by more than 50%. This disease is difficult to control, because it can form spores that can survive in the soil for a long time, and are saprophytic on the remains of other plants. This study was conducted to determine the effect of the application of 5 kinds of Actinomycetes isolates (SW13, SW5, BYM1, BYM4, and SIO 5), with 3 kinds of concentrations (5 ml, 10 ml, and 15 ml/plant) on the Mentes variety shallots. Fusarium oxysporum. The results showed that the application of the isolate code SIO5 to the Mentes variety of shallots gave the best effect in suppressing the attack of Fusarium oxysporum by 52.2%. In addition, the suspension of SIO5 isolate also had a positive effect on plant height of 41.5 cm, number of tillers of 8.89, and tuber weight of 42.84 grams. While the type of concentration did not have a good effect on the incidence of disease, plant height, and the number of tillers and tuber weight.